On the ``Active spacer and stabilizer'' role of Zn in Cu1-xZnxFe2O4 in the selective mono-N-methylation of aniline: XPS and catalysis study - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Journal of Catalysis, 2006)
A systematic catalytic methylation study on ferrospinel materials led to the selective production of N-methylaniline (NMA) with Cu1-xZnxFe2O4. Aniline methylation was carried out on Cu1-xZnxFe2O4 with a feed composition of CH3OH:PhNH2:H2O = 3:1:1 at 513-633 K. NMA was formed selectively on all of the catalyst compositions, with trace amounts of secondary products under most of the conditions. Cu0.5Zn0.5Fe2O4 composition showed high catalytic activity and stability up to 100 h. Although the Cu2+ was responsible for methylation activity, Zn2+ enhanced the overall stability of the catalyst system. XPS investigations revealed that the degree of Cu2+ reduction decreased dramatically from x = 0.05/0.25 to 0.5/0.75 on spent catalysts. TPR studies indicated that the reducibility of Cu2+ decreased from fully reducible at 523 K with Cu-rich compositions to partially reducible at 573 K on x = 0.5. Stable activity observed on Cu0.5Zn0.5Fe2O4 can be attributed to the highly heterogeneous distribution of metal ions. This heterogeneous distribution indicates an important role of zinc, likely as an ``active spacer cum stabilizee' that hinders the reduction of active Cu2+ and contributes to prolonged activity. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Aniline; Ferrite; N-methylaniline; N-methylation; spacer; stabilizer; surface distribution; TPR; XPS

Selective production of methoxyphenols from dihydroxybenzenes on alkali metal ion-loaded MgO - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Journal of Catalysis, 2006)
Selective O-methylation of dihydroxybenzenes (DHBs; catechol, resorcinol, and hydroquinone) to methoxyphenols (MPs) was carried out with dimethylcarbonate on MgO and alkali metal ion (Li, K, and Cs)-loaded MgO between 523 and 603 K. Catalytic activity and product selectivity varied with respect to DHB substrates. Selectivity for O-methylated products increased with increasing basicity of alkali ions; however, K-MgO showed high and stable activity toward MPs. Selectivity for MPs obtained from three substrates increased in the following order: catechol < resorcinol < hydroquinone. The mode of interaction of substrates on the catalysts surface influenced reactivity and product selectivity. It is likely that the low reaction temperatures used (< 603 K) kinetically control and favor high MP selectivity from DHBs. Calcined and spent catalysts were characterized by XRD, surface area, SEM, thermal analysis, NMR, and XPS. XRD analysis revealed the formation of alkali oxide phases on alkali-loaded MgO. Crystallite size and surface area of the catalysts decreased after methylation reactions, except on K-MgO. TGA showed 4060 wt% coke deposition on spent catalysts. TGA in N-2 followed by air and C-13 CP-MAS NMR measurements indicated the nature of deposited carbon to be molecular species, graphite, MgCO3 and polyaromatics. XPS revealed the nature and availability of active sites on the spent catalysts, as well as the same changes with reaction conditions and correlated with catalytic activity. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: alkali-loaded MgO; dihydroxybenzene; K-MgO; methoxyphenol; MgO; O-methylation; thermal analysis; XPS